Positive plate and battery
By setting a conductive inactive layer between the current collector of the positive electrode sheet and the active material layer, the capacity loss problem caused by the transition zone between the insulating layer and the active material layer is solved, the safety and capacity retention of the battery are improved, and the active material is ensured Effective play.
Patent Information
- Application Number
- CN202310824762.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-06
- Publication Date
- 2025-01-07
AI Technical Summary
During the manufacturing process, the existing positive electrode sheets are difficult to deintercalate lithium ions due to the transition zone between the insulating layer and the active material layer, resulting in loss of the positive electrode active material capacity and reducing the overall capacity of the battery.
The inactive layer is arranged between the current collector and the active material layer of the positive electrode sheet, the ceramic layer is eliminated, and the inactive layer is extended to the position of the ceramic layer to avoid the transition zone between the insulating layer and the active material layer, and the conductive inactive is adopted The layer replaces the insulating layer to ensure that the capacity of the active material layer is exerted.
It effectively avoids capacity loss in the transition zone, improves the safety of mechanical abuse and capacity retention of the battery, reduces the risk of lithium excretion, and improves the thickness uniformity of the positive electrode sheet and the interface firmness near the electrode.
Smart Images

Figure CN119275229A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a positive electrode sheet and a battery. Background Art
[0002] The battery cell with multi-electrode winding and stacking structure has an electrode ear extending from the electrode sheet. In order to prevent burrs from being generated during the manufacturing process and to ensure that the positive electrode active material can be completely covered by the negative electrode active material to prevent lithium precipitation, the current industry practice is to apply an insulating layer on the side of the positive electrode ear to improve safety. The schematic diagram is shown in Figure 9. Fig.9A is a top view of the pole piece. Fig. 9B It is the edge of the pole Fig.9A Left view of the dotted area. On the side of the positive electrode tab, near the edge of the electrode and on the tab, there is usually an insulating layer of 0.5 to 5 mm. The insulating layer and the active material layer penetrate each other, and there is a transition zone of a certain width. The insulating layer and the active material layer are irregularly distributed in the transition zone. Since the insulating layer does not have the ability to conduct electrons, it is difficult for the active material in the transition zone to participate in the electrochemical reaction, and it is difficult to deintercalate lithium ions. The capacity of this part of the positive electrode active material is lost, reducing the overall capacity of the battery. Summary of the invention
[0003] In view of this, the present invention provides a positive electrode sheet and a battery. The positive electrode sheet is provided with an inactive layer between the current collector and the active material layer, which not only has a protective effect on the current collector, but also can avoid the capacity loss in the transition zone and does not affect the capacity of the active material.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a positive electrode sheet, which includes a current collector, an inactive layer, an active material layer and a tab; the inactive layer and the active material layer are arranged on at least one side surface of the current collector, and the inactive layer is arranged between the current collector and the active material layer;
[0006] The active material layer includes active material, and the inactive layer does not include active material;
[0007] Along the extending direction of the electrode tab, the edge of the inactive layer exceeds the edge of the active material layer.
[0008] The present invention eliminates the ceramic layer at the edge of the pole piece close to the pole ear end, and extends the inactive layer to the position where the ceramic layer was originally set, so that there is no transition zone between the inactive layer and the active material layer where the insulating layer and the active material layer penetrate each other, thereby avoiding the capacity loss in the transition zone and not affecting the capacity of the active material.
[0009] In the present invention, the inactive layer is a coating layer that does not provide a lithium source and has a conductive effect.
[0010] Preferably, the distance that the edge of the non-active layer extends beyond the edge of the active material layer vertically is 0.5 to 5 mm.
[0011] In an embodiment of the present invention, the width of the non-active layer is 10.5 to 150 mm, and the width of the active material layer is 10 to 145 mm. However, the present invention is not limited thereto, as long as it is ensured that the distance that the edge of the non-active layer extends beyond the edge of the active material layer vertically is 0.5 to 5 mm.
[0012] In an embodiment of the present invention, at least one surface of the current collector includes a first region and a second region, and the tab is disposed at one end of the current collector close to the first region;
[0013] The non-active layer includes region A and region B. Region A is disposed on the first region and part of the tab surface, and region B is disposed on the second region.
[0014] Preferably, the thickness of region A is greater than or equal to the thickness of region B. More preferably, the thickness of region A is greater than the thickness of region B. This design can more effectively prevent the generation of burrs, more effectively prevent the phenomenon that the positive active material is completely covered by the negative active material, and improve safety.
[0015] Preferably, the thickness of region A is 1 to 50 μm.
[0016] Preferably, the thickness of region A is 5 to 40 μm.
[0017] In a specific embodiment of the present invention, the thickness of region A is 5 to 20 μm.
[0018] Preferably, the thickness of region B is 0.1 to 20 μm.
[0019] Preferably, the thickness of region B is 1 to 10 μm.
[0020] In a specific embodiment of the present invention, the thickness of region B is 1 to 5 μm.
[0021] Preferably, the width of region A is d1, the width of region B is d2, and the width of the active material layer is d3. d1, d2, and d3 satisfy the following relational expression:
[0022] d2 ≤ d3 < d1 + d2.
[0023] In a specific embodiment of the present invention, when d2 = d3, as shown in FIG. 9, the projections of region A and region B in the length direction are both rectangles.
[0024] In another specific embodiment of the present invention, when d2 < d3 < d1 + d2, as Figure 3As shown, the projection of region A in the length direction is a pentagonal right-angled trapezoid, and the projection of region B in the length direction is a rectangle. However, the present invention is not limited thereto, and any technical solution that can realize the concept of the present invention is within the protection scope of the present invention.
[0025] In an embodiment of the present invention, the inactive layer includes inorganic particles not containing lithium and a binder.
[0026] In the embodiment of the present invention, the inorganic particles not containing lithium refer to inorganic particles not containing lithium-containing transition metal oxide.
[0027] Preferably, the mass percentage of the inorganic particles not containing lithium to the binder is (80wt% to 99wt%): (1wt% to 20wt%).
[0028] Preferably, the mass percentage of the inorganic particles not containing lithium to the binder is (90wt% to 99wt%): (1wt% to 10wt%).
[0029] Preferably, the inorganic particles not containing lithium include a conductive material and / or an insulating material.
[0030] Preferably, the inorganic particles not containing lithium include a conductive material, wherein the conductive material includes a first conductive material and / or an insulating material coated with a second conductive material.
[0031] Preferably, the first conductive material includes but is not limited to at least one of ATO (Sb-doped SnO2), FTO (F-doped SnO2), ITO (Sn-doped In2O3), and AZO (Al-doped ZnO).
[0032] Preferably, the second conductive material includes but is not limited to at least one of carbon black, carbon nanotubes, graphene, ATO, FTO, ITO, and AZO.
[0033] In another embodiment of the present invention, the inorganic particles not containing lithium include only insulating materials, and the inactive layer further includes a conductive agent.
[0034] Preferably, the conductive agent includes but is not limited to at least one of carbon black, carbon nanotubes, graphene, and carbon fiber.
[0035] Preferably, the insulating material includes but is not limited to at least one of aluminum oxide, magnesium oxide, titanium oxide, zinc oxide, silicon oxide, boehmite, cobalt oxide, iron phosphate, aluminum phosphate, iron metaphosphate, and aluminum metaphosphate.
[0036] Preferably, the adhesive includes but is not limited to at least one of polyvinylidene fluoride (PVDF), acrylic acid-modified PVDF, polyacrylate polymers, polyacrylic acid, polyacrylic salt, polyimide, styrene-butadiene rubber, and styrene-acrylic rubber.
[0037] In an embodiment of the present invention, the inorganic particles not containing lithium are conductive materials, and the mass percentage of the inorganic particles not containing lithium to the binder is (80wt% to 99wt%): (1wt% to 20wt%). Preferably, the mass percentage of the inorganic particles not containing lithium to the binder is (90wt% to 99wt%): (1wt% to 10wt%).
[0038] In an embodiment of the present invention, the inorganic particles not containing lithium are insulating materials, the inactive layer further comprises a conductive agent, and the mass percentages of the inorganic particles not containing lithium, the conductive agent and the adhesive are (70wt% to 98wt%): (1wt% to 15wt%): (1wt% to 15wt%). Preferably, the mass percentages of the inorganic particles not containing lithium, the conductive agent and the adhesive are (80wt% to 98wt%): (1wt% to 10wt%): (1wt% to 10wt%).
[0039] In the embodiment of the present invention, in the insulating material coated with the second conductive material, the second conductive material and the insulating material can be composed of any proportion, and the coating can be complete or incomplete. Preferably, the mass ratio of the second conductive material to the insulating material is (1-10): (80-98).
[0040] In an embodiment of the present invention, the active material layer includes a positive electrode active material, and the positive electrode active material is a transition metal oxide containing lithium;
[0041] Preferably, the lithium-containing transition metal oxide includes but is not limited to at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium manganese oxide, and lithium-rich manganese-based materials;
[0042] Preferably, the active material layer in the positive electrode sheet further includes a conductive agent and / or a binder.
[0043] Preferably, the mass percentage of each component in the positive electrode active material layer is: 80wt% to 99.8wt% of positive electrode active material, 0.1wt% to 10wt% of conductive agent, and 0.1wt% to 10wt% of binder.
[0044] Preferably, the mass percentage of each component in the positive electrode active material layer is: 90wt% to 99.6wt% of positive electrode active material, 0.2wt% to 5wt% of conductive agent, and 0.2wt% to 5wt% of binder.
[0045] The present invention also provides a method for preparing the positive electrode sheet, comprising the following steps:
[0046] (1) mixing an inactive layer material and a solvent to obtain an inactive layer slurry, and coating the inactive layer slurry on a current collector;
[0047] (2) The active material layer material and the solvent are mixed to obtain an active material layer slurry, and the active material layer slurry is coated on the inactive layer of the current collector. After drying, rolling, and die-cutting the tabs, a positive electrode sheet is obtained.
[0048] In an embodiment of the present invention, the inactive layer is prepared by gravure coating.
[0049] In an embodiment of the present invention, the mesh size of the gravure coating of the preparation area A is 10 to 80 meshes.
[0050] In an embodiment of the present invention, the mesh number of the gravure coating of the preparation area B is 100 to 150 meshes.
[0051] In an embodiment of the present invention, the current collector is a material containing aluminum.
[0052] Preferably, the aluminum-containing material includes one of aluminum foil, carbon-coated aluminum foil, and aluminum-polymer composite current collector.
[0053] The present invention also provides a battery, which comprises a negative electrode sheet, a separator and the positive electrode sheet.
[0054] In an embodiment of the present invention, the vertical distance between the projected edge of the negative electrode sheet on one side of the pole ear in the length direction and the projected edge of the inactive layer in the positive electrode sheet on one side of the pole ear in the length direction is d4, and the vertical distance between the projected edge of the active material layer in the positive electrode sheet on one side of the pole ear in the length direction and the projected edge of the inactive layer in the positive electrode sheet on one side of the pole ear in the length direction is d5, and d4 and d5 satisfy the following relationship:
[0055] d4 <d5。
[0056] In the embodiment provided by the present invention, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer coated on one side or both sides of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material, a conductive agent and a binder.
[0057] Preferably, the mass percentage of each component in the negative electrode active material layer is: 80wt% to 99.8wt% of the negative electrode active material, 0.1wt% to 10wt% of the conductive agent, and 0.1wt% to 10wt% of the binder.
[0058] Preferably, the mass percentage of each component in the negative electrode active material layer is: 90wt% to 99.6wt% of the negative electrode active material, 0.2wt% to 5wt% of the conductive agent, and 0.2wt% to 5wt% of the binder.
[0059] Preferably, the negative electrode active material includes a carbon-based negative electrode material.
[0060] Preferably, the carbon-based negative electrode material includes at least one of artificial graphite, natural graphite, mesophase carbon microspheres, hard carbon, and soft carbon.
[0061] Preferably, the negative electrode active material may further include a silicon-based negative electrode material.
[0062] Preferably, the silicon-based negative electrode material is selected from at least one of nano-silicon, silicon oxide negative electrode material (SiOx, 0 < x < 2), or silicon-carbon negative electrode material.
[0063] Preferably, in the negative electrode active material, the mass ratio of the carbon-based negative electrode material to the silicon-based negative electrode material is 10:0 to 1:19.
[0064] In a specific embodiment provided by the present invention, the negative electrode current collector is a copper foil.
[0065] In an embodiment of the present invention, in the positive electrode sheet or the negative electrode sheet, the conductive agent is selected from at least one of conductive carbon black (acetylene black and / or Ketjen black), conductive graphite, conductive carbon fiber, carbon nanotube, metal powder, and carbon fiber.
[0066] In an embodiment of the present invention, in the positive electrode sheet or the negative electrode sheet, the binder is selected from at least one of PVDF, sodium carboxymethyl cellulose, styrene-butadiene rubber, polytetrafluoroethylene, and polyethylene oxide.
[0067] The present invention also provides a method for preparing the above battery, including the following steps:
[0068] Stack the positive electrode sheet, the separator, and the negative electrode sheet to obtain a stacked core, or wind the positive electrode sheet, the separator, and the negative electrode sheet after stacking to obtain a wound core, place the stacked core or the wound core in an outer package, inject an electrolyte into the outer package, and perform vacuum packaging, standing, and formation to obtain the battery of the present invention.
[0069] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0070] (1) In the positive electrode sheet of the present application, the non-active layer is located between the current collector and the active material layer, which has a protective effect on the current collector and further improves the mechanical abuse safety of the battery.
[0071] (2) In the positive electrode sheet of the present application, the protective layer uses a conductive non-active layer to replace the insulating layer at the edge of the positive electrode tab side, avoiding the capacity loss of the transition zone and not affecting the capacity performance of the active material.
[0072] (3) The non-active layer in the positive electrode sheet of the present application does not include a lithium-containing transition metal oxide, and due to the setting of the non-active layer region A, the width region of the non-active layer exceeds the width region of the positive electrode active material layer, reducing the risk of lithium deposition.
[0073] (4) The thickness of the inactive layer region A in the positive electrode sheet of the present application is greater than the thickness of region B, the thickness uniformity of the positive electrode sheet is better, the interface between the positive electrode sheet near the tab and the diaphragm and the negative electrode sheet is stronger, and the capacity retention rate is higher. BRIEF DESCRIPTION OF THE DRAWINGS
[0074] Figure 1 Left side view of the positive electrode sheet of Example 1;
[0075] Figure 2 Distribution diagram of the first and second regions of the current collector in Example 1;
[0076] Figure 3 Left side view of the positive electrode sheet of Example 1;
[0077] Figure 4 Schematic diagram of the cross-section of the battery cell structure;
[0078] Figure 5 Schematic diagram of the core structure;
[0079] Fig. 6A Top view of the positive electrode undercoat before die-cutting the tabs;
[0080] Figure 6B Top view of the positive electrode after die-cutting the tabs;
[0081] Figure 7 Left side view of the positive electrode sheet of Example 9;
[0082] Figure 8 Left side view of the positive electrode sheet of Example 11;
[0083] Fig.9A Comparative Example 1: Top view of the positive electrode sheet;
[0084] Fig. 9B Comparative Example 1 Positive electrode sheet Fig.9A Left view of the dashed area.
[0085] The reference numerals are as follows:
[0086] Positive electrode sheet 100, positive electrode current collector 110, inactive layer 120, active material layer 130, edge 131 of active material layer, positive electrode tab 140, first region 111, second region 112, region A 121, region B 122, edge 123 of inactive layer, insulating protective layer 150, transition layer 160;
[0087] Diaphragm 200;
[0088] A negative electrode sheet 300, a negative electrode tab 340;
[0089] The X pole piece is in the thickness direction, and the Y pole piece (current collector, inactive layer or active material layer) is in the extension direction or width direction along the pole ear. DETAILED DESCRIPTION
[0090] The present invention discloses a positive electrode sheet and a battery. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0091] The reagents, instruments or materials used in the present invention can be obtained through commercial channels.
[0092] The present invention will be further described below in conjunction with embodiments:
[0093] Example 1
[0094] 1. Battery structure
[0095] The battery of this embodiment includes a positive electrode sheet 100, a separator 200, a negative electrode sheet 300 and an electrolyte;
[0096] like Figure 1 As shown, the positive electrode sheet 100 (only the coating structure on one side of the positive electrode sheet is shown, and the inactive layer and active layer structure on the other side are not shown) includes a current collector 110, an inactive layer 120, an active material layer 130 and a tab 140; the inactive layer and the active material layer are disposed on both sides of the current collector, and the inactive layer is disposed between the current collector and the active material layer;
[0097] like Figure 2 As shown, the surfaces of both sides of the current collector include a first region 111 and a second region 112, and the electrode ear is arranged at one end of the current collector close to the first region;
[0098] like Figure 3 As shown ( Figure 3 Only the single-side structure of the positive electrode sheet is shown, and the inactive layer and active layer structure on the other side are not shown). The inactive layer includes region A 121 and region B 122. Region A is arranged in the first region and part of the lug surface, and region B is arranged in the second region. The thickness of region A is greater than the thickness of region B.
[0099] The width of the inactive layer is 102.5 mm, the width of the active material layer is 100 mm, and the vertical distance that the edge of the inactive layer exceeds the edge of the active material layer is 2.5 mm.
[0100] The width of region A is d1, the width of region B is d2, and the width of the active material layer is d3. d1, d2, and d3 satisfy the following relationship:
[0101] d2≤d3 <d1+d2。
[0102] like Figure 4 As shown, a cross-sectional schematic diagram of a battery cell structure composed of a positive electrode sheet 100, a separator 200, and a negative electrode sheet 300 (the negative electrode tab is not shown);
[0103] The vertical distance between the projection edge of the negative electrode sheet on the side of the pole ear in the length direction and the projection edge of the inactive layer in the positive electrode sheet on the side of the pole ear in the length direction is d4.
[0104] The vertical distance between the projection edge of the active material layer on the side of the pole ear in the length direction of the positive electrode sheet and the projection edge of the inactive layer on the side of the pole ear in the length direction of the positive electrode sheet is d5, and d4 and d5 satisfy the following relationship:
[0105] d4 <d5。
[0106] The schematic diagram of the core structure is as follows Figure 5 shown.
[0107] 2. Preparation method
[0108] Step 1: Prepare the inactive layer slurry, mix 97% by weight of ATO-coated TiO2 (the amount of ATO is 3%, the amount of TiO2 is 94%) and 3% by weight of PVDF, add a certain amount of NMP, adjust the solid content of the slurry to 40%, and prepare it into a slurry after stirring.
[0109] Step 2: Prepare positive electrode slurry, mix 96% by weight of lithium cobalt oxide, 1% by weight of carbon black + 1% by weight of carbon nanotubes, and 2% by weight of PVDF, add a certain amount of NMP, adjust the solid content of the slurry to 70%, and stir to prepare the positive electrode slurry.
[0110] Step 3: Prepare negative electrode slurry, mix 96% by weight of artificial graphite, 1% by weight of carbon black, 1.5% by weight of styrene-butadiene rubber + 1.5% by weight of sodium carboxymethyl cellulose, add deionized water, adjust the solid content of the slurry to 40%, and prepare negative electrode slurry by stirring.
[0111] Step 4: Preparation of positive electrode sheet. The inactive layer slurry of step 1 is coated on aluminum foil by gravure coating (the gravure roller is prepared by engraving different meshes in different areas, and the engraving area of the corresponding inactive layer area A is 40 mesh, and the engraving area of area B is 120 mesh) to obtain a positive electrode base coating. The thickness of the inactive layer of the base coating varies in different areas, where the thickness of area A is 20μm, the thickness of area B is 5μm, and the thickness of area A near one end of area B shows a gradual trend. In the left view of the positive electrode sheet, area A is a pentagonal right-angled trapezoid, and area B is a rectangle. Then the positive active material of step 2 is coated on the inactive layer, and the positive electrode sheet is obtained after drying, such as Fig. 6A .
[0112] Step 5: Preparation of negative electrode sheet: coating the negative electrode slurry in step 3 on copper foil through extrusion coating process to obtain a negative electrode sheet.
[0113] Step 6: Roll the positive and negative electrode sheets to the designed thickness, and then die-cut the tabs. The schematic diagram of the positive electrode sheet after die-cutting the tabs is as follows: Figure 6B shown.
[0114] Step 7: Place the diaphragm between the positive and negative electrode sheets and wind them to obtain a roll core. Use external Al (aluminum) tabs to weld the tabs of the positive electrode sheet together. Use external nickel-plated copper tabs to weld the tabs of the negative electrode sheet together. Use aluminum-plastic film to encapsulate the roll core and inject electrolyte.
[0115] Step 8: Use lithium-ion battery formation equipment to charge and discharge the battery cells to harden them and sort out the capacity of the battery cells.
[0116] Step 9: The battery cell is sealed for the second time and folded to make the battery cell basically formed.
[0117] Step 10: Perform an OCV test on the battery to determine the K value of the battery and select products with qualified K values.
[0118] Example 2
[0119] The component of the inactive layer is AZO-coated TiO2, and the rest is the same as in Example 1.
[0120] Example 3
[0121] The inactive layer component is ATO, and the rest is the same as in Example 1.
[0122] Example 4
[0123] The inactive layer component is AZO, and the rest is the same as in Example 1.
[0124] Example 5
[0125] The composition of the inactive layer is 97% carbon black-coated Al2O3 (the amount of carbon black is 3%, the amount of Al2O3 is 94%) + 3% PVDF, and the rest is the same as Example 1.
[0126] Example 6
[0127] The composition of the inactive layer is 94% Al2O3+3% carbon black+3% PVDF, and the rest is the same as in Example 1.
[0128] Example 7
[0129] The thickness of the inactive layer region A is 20 μm, the thickness of the region B is 3 μm, and the rest is the same as in Example 1.
[0130] Example 8
[0131] The thickness of the inactive layer region A is 20 μm, the thickness of the region B is 1 μm, and the rest is the same as in Example 1.
[0132] Example 9
[0133] The thickness of the inactive layer region A is 5 μm, the thickness of B is 5 μm, and the rest is the same as in Example 1. Figure 7 shown.
[0134] Example 10
[0135] The inactive layer and the active material layer are arranged on one surface of the current collector, and the rest is the same as in Example 1.
[0136] Embodiment 11
[0137] like Figure 8 As shown, both region A and region B are rectangular, and the rest are the same as in embodiment 1.
[0138] Example 12
[0139] The width of the inactive layer is 10.5 mm, the width of the active material layer is 10 mm, and the vertical distance from the edge of the inactive layer to the edge of the active material layer is 0.5 mm. Others are the same as in Example 1.
[0140] Example 13
[0141] The width of the inactive layer is 150 mm, the width of the active material layer is 145 mm, and the vertical distance from the edge of the inactive layer to the edge of the active material layer is 5 mm. Others are the same as in Example 1.
[0142] Comparative Example 1
[0143] The positive electrode sheet does not contain an inactive layer, and the insulating protective layer near the tab is boehmite + PVDF (the mass ratio of boehmite to PVDF is 9:1), and its structure is shown in FIG9 , and the rest is the same as in Example 1.
[0144] Comparative Example 2
[0145] The thickness of the inactive layer region A is 20 μm, the thickness of the region B is 0 μm, and the rest is the same as in Example 1.
[0146] Comparative Example 3
[0147] The width of the inactive layer is 75 mm, the width of the active material layer is 75 mm, and the edge of the inactive layer is flush with the edge of the active material layer. Others are the same as in Example 1.
[0148] Battery performance test
[0149] (1) Acupuncture test:
[0150] Fully charge the lithium-ion battery and then place it on the test bench of the needle puncture test equipment. A tungsten steel needle with a diameter of 3mm and a needle tip length of 3.62mm is inserted through the middle of the battery at a speed of 100mm / s. If the battery does not catch fire or explode, the test is considered to have passed. The number of passes / the number of tests is the needle puncture pass rate, and the number of tests is 30.
[0151] (2) Energy density:
[0152] Charge the lithium-ion battery to an upper voltage of 4.45V, then discharge it at 0.2C to a lower voltage of 3.0V. The discharge energy is recorded as E. Then calculate the energy density of the lithium-ion battery using the following formula:
[0153] Energy density = E / (length × width × height of lithium-ion battery).
[0154] (3) Capacity retention after 500 cycles at 45°C:
[0155] The lithium-ion battery is placed in a constant temperature environment of 45°C and charged and discharged at the designed charge and discharge rate for 500 cycles. The first discharge capacity is recorded as C1, and the 500th discharge capacity is recorded as C500. The capacity retention rate after 500 cycles at 45°C is C500 / C1.
[0156] (4) Lithium precipitation
[0157] The battery was cycled at 25°C and 3C / 0.7C charge and discharge conditions, and disassembled at 200T\700T to confirm the degree of lithium deposition. 0, 1, 2, 3, 4, and 5 were used to represent the degree of lithium deposition. The larger the value, the more serious the lithium deposition.
[0158] Table 1 is the comparative data of the inactive layer composition, inactive layer thickness, needle penetration rate, energy density and capacity retention rate after 500 cycles at 45°C of each embodiment and comparative example.
[0159] Table 1 Comparison of different embodiments and comparative examples
[0160]
[0161]
[0162] In Examples 1-13, compared with Comparative Example 1, an inactive layer is provided between the active material layer and the current collector, and the needle puncture pass rate is improved, wherein when the thickness of the inactive layer exceeds 3 μm, the improvement is obvious.
[0163] Compared with Comparative Example 1, Comparative Example 2 has no inactive layer between the active material layer and the current collector, and the conductive inactive layer is near the pole ear, while the insulating layer is near the pole ear in Comparative Example 1. The capacity of Comparative Example 2 is higher than that of Comparative Example 1, and the energy density is increased by 5Wh / L.
[0164] Compared with Example 9, the thickness of the inactive layer region A in Example 1 is greater than the thickness of the inactive layer region B, the thickness uniformity of the positive electrode sheet is better, the interface between the positive electrode sheet and the separator and the negative electrode sheet near the tab is stronger, and the capacity retention rate is higher.
[0165] Compared with Example 6, the inorganic particles in the inactive layer of Example 5 are made of conductive materials. Compared with the design of insulating material inorganic particles + conductive agent in Example 6, Example 5 uses conductive agent to coat inorganic particles of insulating material. The conductive stability of the inactive layer is better and the high-temperature cycle capacity retention rate is better, which is a preferred formula design.
[0166] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A positive electrode sheet, characterized in that: The positive electrode sheet comprises a current collector, an inactive layer, an active material layer and a tab; the inactive layer and the active material layer are arranged on at least one side of the current collector, and the inactive layer is arranged between the current collector and the active material layer; The active material layer includes active material, and the inactive layer does not include active material; Along the extending direction of the electrode tab, the edge of the inactive layer exceeds the edge of the active material layer.
2. The positive electrode sheet according to claim 1, characterized in that: The vertical distance that the edge of the inactive layer exceeds the edge of the active material layer is 0.5 to 5 mm.
3. The positive electrode sheet according to claim 1, characterized in that: At least one side surface of the current collector includes a first region and a second region, and the electrode tab is arranged at one end of the current collector close to the first region; The inactive layer includes region A and region B, wherein region A is arranged in the first region and a portion of the surface of the tab, and region B is arranged in the second region; The thickness of region A is greater than or equal to the thickness of region B; Preferably, the thickness of region A is 1 to 50 μm; Preferably, the thickness of region B is 0.1 to 20 μm.
4. The positive electrode sheet according to claim 2, characterized in that: The width of the region A is d1, the width of the region B is d2, and the width of the active material layer is d3. d1, d2, and d3 satisfy the following relationship: d2≤d3 <d1+d2。 5. The positive electrode sheet according to claim 1, characterized in that: The inactive layer includes inorganic particles not containing lithium and a binder; Preferably, the inorganic particles not containing lithium include conductive materials and / or insulating materials.
6. The positive electrode sheet according to claim 5, characterized in that: The inorganic particles not containing lithium include a conductive material, wherein the conductive material includes a first conductive material and / or an insulating material coated with a second conductive material; And / or, the first conductive material includes at least one of ATO, FTO, ITO, and AZO; And / or, the second conductive material includes at least one of carbon black, carbon nanotubes, graphene, ATO, FTO, ITO, and AZO.
7. The positive electrode sheet according to claim 5, characterized in that: The inorganic particles not containing lithium only include insulating materials, and the inactive layer also includes a conductive agent; Preferably, the conductive agent includes at least one of carbon black, carbon nanotubes, graphene and carbon fiber.
8. The positive electrode sheet according to any one of claims 5 to 7, characterized in that: The insulating material includes at least one of aluminum oxide, magnesium oxide, titanium oxide, zinc oxide, silicon oxide, boehmite, cobalt oxide, iron phosphate, aluminum phosphate, iron metaphosphate, and aluminum metaphosphate; And / or, the adhesive includes at least one of PVDF, acrylic acid-modified PVDF, polyacrylate polymers, polyacrylic acid, polyacrylic salt, polyimide, styrene-butadiene rubber, and styrene-acrylic rubber.
9. The positive electrode sheet according to claim 1, characterized in that: The active material layer includes a positive electrode active material, and the positive electrode active material is a transition metal oxide containing lithium; Preferably, the lithium-containing transition metal oxide includes at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium manganese oxide, and lithium-rich manganese-based materials; The current collector is a material containing aluminum; Preferably, the aluminum-containing material includes one of aluminum foil, carbon-coated aluminum foil, and aluminum-polymer composite current collector.
10. A battery, characterized in that: The battery comprises a negative electrode sheet, a separator and a positive electrode sheet according to any one of claims 1 to 9; and / or, the vertical distance between the projection edge of the negative electrode sheet on one side of the electrode ear in the length direction and the projection edge of the inactive layer in the positive electrode sheet on one side of the electrode ear in the length direction is d4, The vertical distance between the projection edge of the active material layer on the side of the pole ear in the length direction of the positive electrode sheet and the projection edge of the inactive layer on the side of the pole ear in the length direction of the positive electrode sheet is d5, and d4 and d5 satisfy the following relationship: d4 <d5。